MODEL INTEGRATIF DISIPLIN KERJA PNS : BUKTI EMPIRIS DARI INSTANSI PEMERINTAH PROVINSI JAWA TENGAH - Agus Lifandana (Value Added : Majalah Ekonomi dan Bisnis, 2025)
This study aims to investigate the impact of transformational leadership, work culture, and work-life balance on work discipline, with sustainable commitment serving as an intervening variable. The study focuses on civil servants at the Central Office of the Department of Manpower and Transmigration of Central Java Province. A quantitative method was used in this research. The population and sample in this study consist of all civil servants at the Central Office of the Department of Manpower and Transmigration of Central Java Province, totaling 95 respondents, using a census approach. This study involves several variables, namely transformational leadership, work culture, and work-life balance. Several tests were conducted, including the measurement model (outer model), structural model (inner model), and indirect effect tests, with data processed using the SmartPLS application. The findings of this research show that transformational leadership, work culture, work-life balance, and sustainable commitment have a positive and significant effect on work discipline. Sustainable commitment can mediate the influence of transformational leadership, work culture, and work-life balance on work discipline. Keywords: transformational leadership, work culture, work-life balance, continuance commitment, work discipline